Development of Contextual Training-based Module for Building Construction - Hisham, Balqis; awang, Halizah (Research and Innovation in Technical and Vocational Education and Training, 2022)
This study was conducted to develop a Learning Module with the Concept of Contextual Training on Building Structure Construction and identify the Learning Module's suitability for curriculum demands. The design of this study is based on the Sidek Model. The objective of the study is to produce a learning module with the concept of contextual training for the topic of Building Structure Construction according to the suitability of the format and the validity of the content. This study consists of 40 students of Sekolah Menengah Teknik Bukit Piatu who majored in Civil Engineering. This study shows that the Contextual Training-based Module in building construction was suitable as a learning module used by Form 4 Students of Sekolah Menengah Teknik Bukit Piatu. The developed contextual training-based module meets the content criteria and can be accepted by students as a learning module as can help students understand the topic more effectively theoretically and practically.